Neoteric FT-IR investigation on the functional groups of phosphonium-based deep eutectic solvents - Aissaoui, T. (Elsevier B.V., 2015)
Deep eutectic solvents (DESs) are novel solvent media that are currently under investigation as an alternative to ionic liquids and conventional solvents. The physical properties of DESs as well as their mild environmental footprint and potentially critical industrial application necessitate understanding the interaction of functional groups on both the salt and hydrogen bond donor (HBD). In this study, four DESs were prepared by mixing triethylenglycol, diethylenglycol, ethylenglycol, and glycerol as HBDs with methyltriphenylphosphonium bromide as a salt at a molar ratio of 1:4. Fourier transform infrared spectroscopy was conducted to highlight the chemical structure and mechanism of the combination of the four DESs. New spectra illustrating the combination of the functional groups of the HBDs and salt were observed and interpreted. This study is the first to investigate the properties of neoteric phosphonium-based DESs. Â© 2015 Elsevier B.V. All rights reserved.